Phytoradiotherapy to enhance cancer treatment outcomes with cannabidiol, bitter melon juice, and plant hemoglobin - Alfonzetti, Tyler; Moreau, Michele; Yasmin-Karim, Sayeda; Ngwa, Wilfred; Avery, Stephen; Goia, Denisa (Frontiers in Oncology, 2023)
Despite technological advances in radiation therapy for cancer treatment, many patient populations still experience mediocre survival percentages, local control, and quality of life. Additionally, much of the world lacks access to expensive, modern treatment options. The need for innovative, cost-effective solutions that can improve patient treatment outcomes is essential. Phytomedicines have been shown to induce apoptotic tumor cell death, diminish tumor progression, reduce cancer incidence, alleviate harmful hypoxic conditions, and more. While an ample amount of research is available that characterizes many phytomedicines as having anti-cancer properties that increase tumor cell killing/control and mitigate the harmful side effects of radiation damage, little work has been done to investigate the synergistic effect of phytoradiotherapy: combining radiation treatment with phytomedicines. In this study, a protocol for testing the radiosensitizing effects of phytomedicines was validated and used to investigate the well-known plant based medicine cannabidiol (CBD) and the lesser-known medicinal fruit Bitter Melon. Additionally, based on its high concentration of plant hemoglobin which has been shown to abate hypoxia, the African-indigenous Justicia plant was tested in pancreatic adenocarcinoma mouse models. The studies reveal that these phytomedicines can effectively enhance tumor cell killing, minimize tumor growth, and prolong mice survival. There is certainly the need for additional research in this regard, however, phytoradiotherapy: the use of phytomedicines to enhance radiation therapy treatment outcomes, continues to show potential as a promising, innovative way to improve cancer care.